Cruzando fronteiras curriculares: a educação física sob o enfoque cultural na ótica de docentes de escolas municipais de São Paulo - Françoso, Saulo (2011)
The document Orientações Curriculares e Proposição de Expectativas de Aprendizagem para o Ensino Fundamental Ciclo II (Curriculum Guidelines and Proposition of Learning Expectations for Elementary School) of Physical Education, developed in 2007 by Secretaria Municipal de Educação de São Paulo (Municipal Secretariat of Education in the city of São Paulo), presents this area of knowledge within the cultural concept. After the analysis of this document, we found that the conception defended by the curriculum has been strongly influenced by the theories of Critical Multiculturalism and Cultural Studies. Quality-natured, this work aims at investigating, through semi-structured interviews, the perception of five Physical Education teachers of the difficulties and possibilities in the development of classes based on the cultural perspective. By comparing the data obtained in the interviews with the multicultural curriculum theory, it was possible to understand the curriculum as a field of cultural production permeated with power relations, in which teachers face a constant struggle, in school life, to break boundaries in the viability of the official curriculum, since the formal education is hegemonic and still impregnated by the homogenizing, repetitive and monocultural practices. The main difficulties pointed out by the teachers refer to the resistance from students, other teachers and management professionals concerning the cultural curriculum in Physical Education. This resistance is caused due to different factors, such as: the lack of a political pedagogical project aimed at multicultural issues, the politics of deficient training held by the SME/SP (Municipal Secretariat of Education in the city of São Paulo), the misrepresentation by the students concerning the area of knowledge and the school rigid structure. These factors make teachers isolated, delimiting a frontier region that needs to be crossed. Nevertheless, in this interplay of forces, this research has identified several pedagogical potentialities for the cultural curriculum in Physical Education, which can stimulate the teachers and radical researchers productions, involved in the battle for a more equitable, democratic and caring education. Among them, we can highlight the students enhancement towards Physical Education and its importance in school curriculum, the legitimacy of multiple identities which color the classroom environment, the search for alliances with professionals from other areas, open spaces for the families and community in general, the putting down of oppressive relationships of any kind, as well as the possibility for the students to recognize themselves as producers of knowledge